Cellular antioxidant potential and inhibition of foodborne pathogens by a sesquiterpene ilimaquinone in cold storaged ground chicken and under temperature-abuse condition. (30th March 2022) - Bajpai, Vivek K.; Bahuguna, Ashutosh; Kumar, Vishal; Khan, Imran; Alrokayan, Salman H.; Khan, Haseeb A.; Simal-Gandara, Jesus; Xiao, Jianbo; Na, MinKyun; Sonwal, Sonam; Lee, Hoomin; Kim, Myunghee; et al.
Highlights: A sesquiterpene quinone, ilimaquinone was isolated and characterized. Ilimaquinone compromised membrane permeability of foodborne pathogens. Ilimaquinone caused increasing release of ATP, K + ions, and genetic material. Ilimaquinone reduced bacterial count in ground chicken meat at 4 °C and 10 °C. Ilimaquinone did not affect the sensory quality of chicken meat. Abstract: A sesquiterpene quinone, ilimaquinone, was accessed for its cellular antioxidant efficacy and possible antimicrobial mechanism of action against foodborne pathogens ( Staphylococcus aureus and Escherichia coli ) in vitro and in vivo . Ilimaquinone was found to be protective against H2 O2 -induced oxidative stress as validated by the reduction in the ROS levels, including increasing expression of SOD1 and SOD2 enzymes. Furthermore, ilimaquinone evoked MIC against S. aureus and E. coli within the range of 125–250 µg/mL. Ilimaquinone established its antimicrobial mode of action against both tested pathogens as evident by bacterial membrane depolarization, loss of nuclear genetic material, potassium ion, and release of extracellular ATP, as well as compromised membrane permeabilization and cellular component damage. Also, ilimaquinone showed no teratogenic effect against zebrafish, suggesting its nontoxic nature. Moreover, ilimaquinone significantly reduced the S. aureus count without affecting the sensory properties and color values of cold-storaged ground chicken meat even under temperature abuse condition.